Knowledge and Power: Exploring Unproductive Interplay Between Quantitative and Qualitative Researchers. (April 2013) - Lunde, Åshild; Heggen, Kristin; Strand, Roger
This article is concerned with how the development of mixed methods research is influenced by the many aspects of human interplay occurring between researchers representing different disciplines. It examines findings from interviews, field notes, and written documentation from a case study involving a team of health science researchers doing mixed methods research on athletes with knee injuries. The researchers experienced that they did not succeed in integrating quantitative and qualitative data collected from this research. From the collected data, a multiplicity of forms of interplay is identified and discussed. The article suggests that more attention needs to be given to power relations as an important aspect of collaboration between researchers belonging to different epistemic cultures.